2002
DOI: 10.1194/jlr.m200077-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The N-linked oligosaccharides at the amino terminus of human apoB are important for the assembly and secretion of VLDL

Abstract: We determined the role of N-linked glycosylation of apolipoprotein B (apoB) in the assembly and secretion of lipoproteins using transfected rat hepatoma McA-RH7777 cells expressing human apoB-17, apoB-37, and apoB-50, three apoB variants with different ability to recruit neutral lipids. Substituting Asn residue with Gln at the single glycosylation site within apoB-17 (N 158 ) decreased its secretion efficiency to a level equivalent to that of wild-type apoB-17 treated with tunicamycin, but had little effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…It is possible that the impaired glycosylation induced by glucosamine causes a conformational change in the apoB-100 molecule, resulting in increased availability of apoB-100 for ubiquitin-proteasomal degradation (3). This observation is well supported by Vukmirica et al (26), who found that the N-glycans at the N terminus of several apoB constructs are required for secretion. In addition, improperly folded apoB-100 molecules could stimulate ER-stress chaperones such as Grp78 (27).…”
Section: Discussionsupporting
confidence: 76%
“…It is possible that the impaired glycosylation induced by glucosamine causes a conformational change in the apoB-100 molecule, resulting in increased availability of apoB-100 for ubiquitin-proteasomal degradation (3). This observation is well supported by Vukmirica et al (26), who found that the N-glycans at the N terminus of several apoB constructs are required for secretion. In addition, improperly folded apoB-100 molecules could stimulate ER-stress chaperones such as Grp78 (27).…”
Section: Discussionsupporting
confidence: 76%
“…Second, the immunoblot bands of single and double mutants of N124Q and N140Q supports the notion that the prominent changes in molecular weights (compared with WT ABCA3) are likely due to the absence of large sugar moiety and not due to the replacement of a single amino acid. Third, because of asparagine's close resemblance to glutamine in both size and structure, the reliability of glutamine for asparagine substitution mutation in the study of N-linked glycosylation is frequently demonstrated in previous studies of glycoproteins (1,39,53,57,63) including other ABC transporters such as the multidrug resistance protein (MRP) (28), ABCC7 (CFTR) (21), and ABCG2 (16,45).…”
Section: Discussionmentioning
confidence: 98%
“…Preparation of Expression Plasmids-The expression plasmids encoding human apoB-100 (39), B-48 (40), and B-17 (41) cDNA, respectively, were prepared as described previously. Numbers following apoB represent the percent of full-length apoB (apoB-100).…”
Section: Methodsmentioning
confidence: 99%